MiR-27a-3p Targets GLP1R to Regulate Differentiation, Autophagy, and Release of Inflammatory Factors in Pre-Osteoblasts via the AMPK Signaling Pathway - Zeng, Zhi; Fei, Liangyu; Yang, Juntao; Zuo, Jun; Huang, Zelin; Li, Hao (Frontiers in Genetics, 2022)
Objective: Osteoporosis is caused by the dysregulation of bone homeostasis which is synergistically mediated by osteoclasts and osteoblasts. MiR-27a-3p is a key inhibitor of bone formation. Hence, unearthing the downstream target gene of miR-27a-3p is of great significance to understand the molecular mechanism of osteoporosis. Methods: Bioinformatics analysis was utilized to find the downstream target gene of miR-27a-3p, and dual-luciferase reporter assay was conducted to validate the interplay of miR-27a-3p and GLP1R. Besides, qRT-PCR, western-blot and enzyme linked immunosorbent assay (ELISA) were employed to verify the impact of miR-27a-3p on GLP1R expression and the differentiation, autophagy and inflammatory response of MC3T3-E1 pre-osteoblasts. Results: Dual-luciferase assay validated that miR-27a-3p directly targeted GLP1R. Additionally, post-treatment of MC3T3-E1 cells with miR-27a-3p mimics resulted in a remarkable decrease in expression levels of GLP1R, cell differentiation marker gene, autophagy marker gene and AMPK. These results indicated that miR-27a-3p targeted GLP1R to inhibit AMPK signal activation and pre-osteoblast differentiation and autophagy, whereas promoting the release of inflammatory factors. Conclusion: The miR-27a-3p/GLP1R regulatory axis in pre-osteoblasts contributes to understanding the molecular mechanism of osteoporosis.